1952
DOI: 10.1111/j.1365-2621.1952.tb16796.x
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ON TENDERNESS OF BEEF. I. RATE OF HEAT PENETRATIONa

Abstract: The factors affecting the tenderness of beef are numerous, and include such diverse items as breeding, feeding and management, anatomy, cellular activity, enzymes, chemical changes, both analytical and physical, and cooking technics. Workers in a number of laboratories have been exploring various of these areas.Beef generally is considered to be tender when first slaughtered, to become less tender with cold storage up to 48 hours, and then gradually to increase in tenderness as the storage period is lengthened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1960
1960
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The supercontraction clots produced by cooking prerigor meat unrestrained have been previously observed with the light microscope by Paul et al (1944Paul et al ( , 1952 and by Ramsbottom and Strandine (1949). Cassens ef al.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The supercontraction clots produced by cooking prerigor meat unrestrained have been previously observed with the light microscope by Paul et al (1944Paul et al ( , 1952 and by Ramsbottom and Strandine (1949). Cassens ef al.…”
Section: Discussionmentioning
confidence: 88%
“…A neg-ative value was obtained for the regression of shearing strength on sarcomere length and a positive value for the regression of shearing strength on fiber diameter. Paul et al (1952) found that steaks rapidly cooked immediately after slaughter were tender, and Marsh (1964) reported that pre-rigor meat cooked in boiling water before the pH dropped noticeably was tender. Again, it is well known aniong hunters and people who slaughter their own animals that pieces of meat taken and cooked before the carcass stiffens are usually tender.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Paul et al (1952) more slowly in a conventional oven. They found the roasts to be least tender soon after slaughter but increasingly more tender as postmortem time lengthened.…”
Section: Introductionmentioning
confidence: 97%
“…Cover et al (1962~) suggested a possible connection between mealiness and the cracks and breaks in the muscle fibers developed during aging of the meat reported by Paul et al ( 1952). The very short muscle fibers reported here could have been cracked or broken before cooking.…”
Section: Resultsmentioning
confidence: 58%